Some solutions to reduce multidimensional poverty (case study in Nghe An province) - Trương Thị Như Nguyệt (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
: In 2020, on the eve of the implementation of the new multidimensional poverty line, the poverty reduction work of Nghe An province continues to face new difficulties. On the basis of analyzing the causes and poverty situation of Nghe An province in 2020, the article proposes some solutions to effectively reduce the rate of poor households, helping poor households to access basic social services and reduce the poverty gap between the lowland and mountainous areas of Nghe An province